2021
DOI: 10.1002/aenm.202003799
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy to Boost Electrocatalytic Nitrogen Reduction on Perovskite Oxides via the Oxygen Vacancies Derived from A‐Site Deficiency

Abstract: pressures (10-30 MPa), but also demands a large deal of H 2 mainly from natural gas reforming which causes abundant consumption of fossil fuels and huge CO 2 emissions. [3-6] As a result, for energy conservation and environmental protection, it is of crucial importance to explore a clean and sustainable route for NH 3 production. Electrocatalytic N 2 reduction reaction (NRR) under ambient conditions has been emerged recently as an attractive strategy for the green synthesis of NH 3 through utilizing inexhausti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 40 publications
5
95
0
Order By: Relevance
“…Angewandte Chemie XPS and iodometric titration were performed to elucidate the correlation between the oxygen vacancies and La-site deficiencies in these four samples.Figure 2a shows O1sXPS spectra of the four samples.T he peaks at about 533.1, 531.6, 530.4, and 528.9 eV were indexed to surface-adsorbed H 2 O, surface-adsorbed O 2 or hydroxyl groups,h ighly oxidative oxygen species (O 2 2À /O À ,c orresponding to oxygen vacancies), and lattice O 2À ,respectively. [27] According to the relative areas of their peaks (Table S3), the concentrations of oxygen vacancies of the L 2Àx Cs amples were calculated to be 0, 36.6 %, 33.8 %, and 35.7 %, respectively (Figure 2b). In the iodometric titration experiments,w eo bserved as imilar change trend of oxygen vacancy concentrations to that in the XPS analysis,w ith the values of 0.9 %( L 2 C), 10.4 % (L 1.9 C), 11.3 %( L 1.8 C), and 11.8 %( L 1.7 C), respectively (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Angewandte Chemie XPS and iodometric titration were performed to elucidate the correlation between the oxygen vacancies and La-site deficiencies in these four samples.Figure 2a shows O1sXPS spectra of the four samples.T he peaks at about 533.1, 531.6, 530.4, and 528.9 eV were indexed to surface-adsorbed H 2 O, surface-adsorbed O 2 or hydroxyl groups,h ighly oxidative oxygen species (O 2 2À /O À ,c orresponding to oxygen vacancies), and lattice O 2À ,respectively. [27] According to the relative areas of their peaks (Table S3), the concentrations of oxygen vacancies of the L 2Àx Cs amples were calculated to be 0, 36.6 %, 33.8 %, and 35.7 %, respectively (Figure 2b). In the iodometric titration experiments,w eo bserved as imilar change trend of oxygen vacancy concentrations to that in the XPS analysis,w ith the values of 0.9 %( L 2 C), 10.4 % (L 1.9 C), 11.3 %( L 1.8 C), and 11.8 %( L 1.7 C), respectively (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5e shows the high‐resolution XPS spectra of the O 1 s core levels of LNCO55‐Air, LNCO55‐Ar, LNCO55‐Ar anode, and LNCO55‐Ar cathode, which can be divided into five characteristic peaks of lanthanum‐oxygen bond (≈528.4 eV for La—O), lattice oxygen species (≈529.8 eV for O 2− ), hydroxyl groups or the surface adsorbed oxygen (≈531.6 eV for —OH or O 2 ), carbon—oxygen bond (≈532.9 eV for C—O), and adsorbed molecular water (≈534.7 eV for H 2 O). [ 44 , 60 ] As the O 1 s spectra are complicated in quaternary perovskites, it is difficult to distinguish the oxygen vacancy concentration directly by XPS. The XPS results of La 4d and Cu 2p in Figure S15 , Supporting Information, showed that all samples only contained Cu 2+ and La 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…These materials only presented inferior performance when compared with La 0.8 Cs 0.2 Fe 0.8 Ni 0.2 O 3− δ and LaFeO 3 . Beyond the cation doping/substitution strategy, post‐treatment by annealing in a reductive atmosphere (5% H 2 /Ar) [ 121 ] or A‐site deficiency [ 26 ] can also create oxygen vacancies in LaFeO 3 and induce efficient NRR catalysis. Further theoretical studies demonstrated that the introduction of oxygen vacancies into LaFeO 3 could not only facilitate the adsorption and activation of the N 2 molecule, but also optimize the reaction pathways through intensifying the interactions between adsorbed species and unsaturated Fe sites.…”
Section: Electrocatalysis Of Nrrmentioning
confidence: 99%
“…Moreover, the creation of oxygen vacancies can be a versatile strategy for developing effective perovskite oxide‐based NRR catalysts with other A or B‐site elements. [ 26 ]…”
Section: Electrocatalysis Of Nrrmentioning
confidence: 99%